2020
DOI: 10.1111/jdi.13334
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of microribonucleic acid‐155 and microribonucleic acid‐29 with type 2 diabetes mellitus, and the prediction and verification of target genes

Abstract: Aims/Introduction Microribonucleic acid‐155 (microRNA155) and microRNA29 are reported to inhibit glucose metabolism in some cell and animal models, but no evidence from susceptible populations that examines the relationship between microRNA155 or microRNA29 and type 2 diabetes mellitus currently exists. Furthermore, target genes regulated by microRNA155 and microRNA29 that affect glucose and lipid metabolism remain unknown. Materials and Methods Human participants were divided into normal weight (n = 72), obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
(34 reference statements)
0
9
0
1
Order By: Relevance
“…In addition, Marcondes et al 16 demonstrated that altered miR-181a in umbilical cord blood cells could be adopted as a biomarker for childhood obesity. Moreover, in the past few years, it has been reported that circulating miRNAs may also play a variety of biological roles, such as in energy homeostasis and metabolic processes 6,17,18 . Three of the candidate miRNAs in this study have been reported to be associated with metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Marcondes et al 16 demonstrated that altered miR-181a in umbilical cord blood cells could be adopted as a biomarker for childhood obesity. Moreover, in the past few years, it has been reported that circulating miRNAs may also play a variety of biological roles, such as in energy homeostasis and metabolic processes 6,17,18 . Three of the candidate miRNAs in this study have been reported to be associated with metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…These microRNAs include miR-27a-5p, miR-27b-5p, miR-146a-5p, miR-378a-3p, miR-155a, miR-223-3p, miR-132-3p, miR-200c-3p, miR181a and miR-125a, which have previously been linked to obesity. 15–20…”
Section: Introductionmentioning
confidence: 99%
“…These microRNAs include miR-27a-5p, miR-27b-5p, miR-146a-5p, miR-378a-3p, miR-155a, miR-223-3p, miR-132-3p, miR-200c-3p, miR181a and miR-125a, which have previously been linked to obesity. [15][16][17][18][19][20] Previous research has linked dysregulation of the gut microbiota to obesity and other metabolic syndromes. 21 The richness of the gut microbiota in obese hosts is lower than that of the normal microflora, and anthocyanin-rich fruit intervention can increase the richness of the gut microbiota and reduce body weight.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, obesity‐associated microRNAs, such as miR‐192, miR‐27a‐3p, and miR‐27b‐3p, can modulate glucose and lipid metabolism in mice 9 . Recent studies have demonstrated that miR‐155 and miR‐29 levels are elevated in the serum of obese and type 2 diabetes mellitus patients, and an overexpression of miR‐155 and miR‐29 in HepG2 cells negatively impacts glucose and lipid metabolism 10 . These results suggest the important role of miRNAs in obesity and related metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%